Production of bioprotein from empty fruit bunch by Aspergillus niger for fish feed application - Nurfarahani Ezeaty Binti Masakhoh (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
There are high demand in food supply especially protein that important component of diets for humans and animals. In this study POMS was used as carbon sources for fermentation enhance by Aspergilus niger UniMAP AA-1. The aim of this research is to find out the optimum bioprotein contents under Solid State Fermentation, (SSF). In addition, it is desired to study the effect of interactions between the process parameters, temperature (30-35 C), moisture content (30-50 % w/w), and inoculum size (5-15 % v/w). The research was first screening using Full Factorial Design and the significant effects of the parameters were further used in Central Composite Design, (CCD) study. The fermentation process was done in 6 days as at days 6 the highest protein productions were obtained. The validation method was run to validate the value of protein content suggested by the solution of the CCD. From the analysis of the variance, (ANOVA) using quadratic polynomial equation, optimum protein content obtained was 1.188 mg/mL by the using substrate concentration of 55.54 % w/w and inoculum size of 12.03 % v/w.